2020
DOI: 10.4315/jfp-20-090
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Suitability of Semicarbazide as an Indicator of Preharvest Nitrofurazone Use in Raw Chicken

Abstract: Semicarbazide (SEM) is the U.S. Food and Drug Administration's official marker for nitrofurazone use in food animals. The U.S. Department of Agriculture Food Safety and Inspection Service conducted a study to evaluate the source of SEM that was identified by a U.S. trading partner in a subset of chicken samples presented for inspection, even though nitrofurazone has been banned from use in U.S. food-producing animals since 2002. The study design included analyses to detect and quantify total and bound SEM in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Some examples of these steps include the following: (1) to address the issue of azodicarbonamide in flour, testing for the marker metabolite for nitrofurazone in breaded food products should be carried out on only the animal tissue part of the product, (2) to address the issue of natural occurrence of SEM in shellfish, only the inner core of products such as shrimps, prawns and crayfish should be tested for the marker metabolite for nitrofurazone, as the naturally occurring SEM occurs only in the outer part and (3) to address the issue of SEM being produced during food processing, the sample should be extensively washed with a range of organic solvents to remove any free SEM from the sample prior to the hydrolysis and derivatisation step for protein‐bound SEM as the marker metabolite for nitrofurazone. The latter step is the one relevant to analysis of products, such as gelatine, for SEM as a marker metabolite of nitrofurazone; however, the finding that SEM generated during food processing may become bound to macromolecules in the food product (Hoenicke et al., 2004; Johnston et al., 2020) renders this step not useful in distinguishing the source of any measured SEM in such samples.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples of these steps include the following: (1) to address the issue of azodicarbonamide in flour, testing for the marker metabolite for nitrofurazone in breaded food products should be carried out on only the animal tissue part of the product, (2) to address the issue of natural occurrence of SEM in shellfish, only the inner core of products such as shrimps, prawns and crayfish should be tested for the marker metabolite for nitrofurazone, as the naturally occurring SEM occurs only in the outer part and (3) to address the issue of SEM being produced during food processing, the sample should be extensively washed with a range of organic solvents to remove any free SEM from the sample prior to the hydrolysis and derivatisation step for protein‐bound SEM as the marker metabolite for nitrofurazone. The latter step is the one relevant to analysis of products, such as gelatine, for SEM as a marker metabolite of nitrofurazone; however, the finding that SEM generated during food processing may become bound to macromolecules in the food product (Hoenicke et al., 2004; Johnston et al., 2020) renders this step not useful in distinguishing the source of any measured SEM in such samples.…”
Section: Assessmentmentioning
confidence: 99%
“…This author also described the formation of SEM in the presence of hydroxyurea. Johnston et al (2020) reported on a study to determine whether SEM was formed in chicken during processing, disinfection, chilling and freezing. The study arose because exported poultry was rejected at the point of entry by a U.S. trading partner due to the presence of SEM and the associated assumption that the SEM was indicative of nitrofurazone use.…”
Section: Possible Sources Of Sem Other Than As a Metabolite Of Nitrof...mentioning
confidence: 99%
“…Further, SEM is naturally produced in shrimp, crayfish, and other crustaceans 6–9 . These reports indicate that SEM cannot be used to reliably confirm nitrofurazone abuse in food‐producing animals 4,5,10 . Therefore a specific marker of nitrofurazone that is capable of differentiating treated and untreated farm animals is highly desired as use of semicarbazide as a marker has impacted trade of animal food products at ports of entry 4,5,10 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Due to risks to human health regulatory agencies including the European Commission, the U.S. Food and Drug Administration, the Thailand Ministry of Health, and the New Zealand Food Safety Authority, have explicitly prohibited the use of nitrofurazone in food-producing animals. 5 Additionally, regulatory agencies monitor the illegal use of, or inadvertent exposure to, nitrofurazone by measuring tissue bound semicarbazide (SEM) because parent nitrofurazone is rapidly metabolized. 5 However several publications have demonstrated that the occurrence of SEM in food is not merely attributable to nitrofurazone use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation